Equilibrium Vacancies in a Labor Market Dominated by Non-Profit Firms: The "Shortage" of Nurses - Hurd, Richard W. (The Review of Economics and Statistics, 1973)
H EALTH professionals have complained of a of Registered Nurses for the past twenty-five years. High vacancy rates have been reported for nursing positions throughout the entire post-World War II period. From 1951 to 1966 an average of 14 per cent of budgeted hospital nursing positions were unfilled.1 Donald Yett and other economists have noted that this state of chronically high vacancy rates might result from an oligopsonistic market structure. This explanation of the shortage of nurses is developed fully below. First, a model of hospital input utilization is presented, viewing hospitals as maximizers of a welfare function representing the goals of hospital management. With the aid of this model it is demonstrated that under a wide range of behavioral assumptions monopsony hospital employers will report vacancies in equilibrium. Second, the monopsony question is put to an empirical tes-t in a multiple regression setting. A significant negative relationship is demonstrated between the wages of nurses and concentration in the hospital sector. This result indicates that where monopsony power is present in the market for nurses, that power will be exploited. The conclusion follows that the high vacancy rates for nursing positions result in part from an oligopsonistic market structure.